The Effects of Patient Occupation, Hobbies, and Body Mass Index on Kneeling after Total Knee Arthroplasty - Sabeh, Karim G.; Hernandez, Victor H.; Cohen-Levy, Wayne B.; Ong, Alvin; Orozco, Fabio; Bennett, Veronica; Post, Zachary (The Journal of Knee Surgery, 2019)
A common patient concern after total knee arthroplasty (TKA) is the ability to kneel. Kneeling may have a substantial impact on the patients' ability to perform many activities of daily living, occupations, and hobbies. The purpose of this study was to quantify the percentage of patients able to kneel after TKA after 2 years and to evaluate preoperative patient characteristics that influence the patient's perceived ability to kneel after TKA such as obesity, occupation, and hobbies. We retrospectively assessed a cohort of 404 patients who underwent primary TKA with patellar resurfacing. We assessed the impact of patient hobbies, occupation, employment status, and body mass index (BMI) on the kneeling capacity and patient-reported satisfaction. Univariate analysis was performed using Fisher's exact test, and multivariate analysis was performed using logistic regression with multiple imputations. A total of 404 patients were included. Sixty percent of patients were unable to kneel after TKA. Males (p < 0.001) and patients with occupations or hobbies requiring kneeling (p < 0.05) were more likely to kneel after surgery. We identified an inverse relationship between BMI and the ability to kneel. No correlation was found between duration and frequency of kneeling relative to patient-reported ease or difficulty with kneeling. Patient-reported factors that prevented patients from kneeling were pain, physical inability, and fear of damaging the prosthesis. Patient education may be helpful in improving patient expectations about kneeling after surgery. A small but significant difference in subjective patient satisfaction was observed when comparing patients able to kneel with those unable to kneel.
Keywords: kneeling; total knee arthroplasty; activities of daily living